2007
DOI: 10.3201/eid1302.061295
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia parkeriInfection after Tick Bite, Virginia

Abstract: We describe a man with a febrile illness and an eschar that developed at the site of a tick bite. Rickettsia parkeri was detected and isolated from the eschar. This report represents the second documented case of R. parkeri rickettsiosis in a US serviceman in eastern Virginia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 10 publications
6
66
0
5
Order By: Relevance
“…The three clinical cases of rickettsiosis reported in the present study presented clinical manifestations similar to previous reported cases due to R. parkeri in the United States; that is mild fever (<40 o C), malaise, headache, rash, inoculation eschar at the tick bite site, regional lymphadenopathy, and no lethality 12,18 . The three cases also presented similar pattern in the serological reactivities to different rickettsial antigens, characterized by higher and similar titers to R. parkeri and R. rickettsii, and substantially lower titers to other rickettsial antigens, including the spotted fever group agents R. felis, R. amblyommii, and R. rhipicephali.…”
Section: Discussionsupporting
confidence: 85%
“…The three clinical cases of rickettsiosis reported in the present study presented clinical manifestations similar to previous reported cases due to R. parkeri in the United States; that is mild fever (<40 o C), malaise, headache, rash, inoculation eschar at the tick bite site, regional lymphadenopathy, and no lethality 12,18 . The three cases also presented similar pattern in the serological reactivities to different rickettsial antigens, characterized by higher and similar titers to R. parkeri and R. rickettsii, and substantially lower titers to other rickettsial antigens, including the spotted fever group agents R. felis, R. amblyommii, and R. rhipicephali.…”
Section: Discussionsupporting
confidence: 85%
“…Other pathogenic rickettsiae exist in nature and may cause human illness. For example, R. parkeri was identified as a human pathogen in 2004 [31][32][33] and was detected in an A. americanum from Knox County, Tennessee in 2007. 34 It is possible that the current human surveillance system overreports RMSF cases based on antibodies, which cross-react against other SFGR, including R. parkeri and R. amblyommii .…”
Section: Discussionmentioning
confidence: 99%
“…Rickettsia parkeri agent is responsible for spotted fever cases in humans in the United States where it is transmitted by Amblyomma maculatum Koch, 1844(PADDOCK et al, 2004, 2008WHITMAN et al, 2007;FORNADEL et al, 2011). This pathogen was also detected in A. maculatum in Peru (FLORES-MANDONZA et al, 2013), A. triste in Uruguay (VENZAL et al, 2004a(VENZAL et al, , 2012PACHECO et al, 2006;CONTI-DÍAZ et al, 2009), Argentina (NAVA et al, 2008a and Brazil (SILVEIRA et al, 2007) andin A. tigrinum in Bolivia (TOMASSONE et al, 2010b).…”
Section: Rickettsia Parkeri and Rickettsia Parkeri-like Strainsmentioning
confidence: 99%